Behavior of childhood eye conditions in the Cienfuegos province. 2019 - Oslaymi Yero Lorente; Manuel Enrique Rodríguez Valdés; Yelenis Abreu Jáuregui; Marta Abreu Velázquez; Layra Pérez Acosta; Yandy Figueredo Ocampo (Medisur)
Background: In pediatric ages, the early diagnosis of any ophthalmic disease is of great relevance, since, if they remain untreated, vision damage will be irreversible, and the consequences, for life. Objective: to describe the behavior of eye conditions in pediatric patients. Methods: an observational, descriptive study was carried out at the Paquito González Cueto Pediatric University Hospital in Cienfuegos. All the patients attended (N = 1404) during the year 2019 were included in the research. The variables: age, sex, ophthalmological diagnosis, type of treatment, and municipality of origin were studied. Results: 51% of patients were female. The most represented ages were those of the group from 4 to 8 years, for 35.4%. Ametropia and strabismus were the most frequent ophthalmological conditions, in 36.4 and 22.7% of cases, respectively. The most performed treatment was optical correction (40.3%), and the municipality of Cienfuegos, the most observed place of residence. Conclusion: eye conditions do not have a marked preference for any sex, although girls attended more during the period studied. The group from 4 to 8 years old, the beginning stage of school life, was the most received in consultation, especially because of ametropia and strabismus; which also explains the greater use of optical correction.